2014
DOI: 10.1038/ajg.2014.71
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effects of Alcohol and Tobacco Consumption on the Risk of Esophageal Squamous Cell Carcinoma: A Meta-Analysis

Abstract: There is a positive synergistic effect of alcohol and tobacco use for ESCC. The observed combined effect of the two factors is almost double if there were no synergy. Efforts for controlling the burden of ESCC should focus on individuals who use both alcohol and tobacco.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(146 citation statements)
references
References 29 publications
4
136
2
4
Order By: Relevance
“…There is a known synergistic effect of alcohol and tobacco consumption on the risk of cancer of the oral cavity, pharynx and esophagus [22][23][24]. For example, the risk of oral cavity and pharynx cancers is about 5-10 times higher for heavy smokers than for nonsmokers, and about 5 times higher for heavy drinkers than for nondrinkers.…”
Section: Discussionmentioning
confidence: 99%
“…There is a known synergistic effect of alcohol and tobacco consumption on the risk of cancer of the oral cavity, pharynx and esophagus [22][23][24]. For example, the risk of oral cavity and pharynx cancers is about 5-10 times higher for heavy smokers than for nonsmokers, and about 5 times higher for heavy drinkers than for nondrinkers.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque la validez de estas excepciones está en revisión, su ocurrencia es motivo de investigación (91) . Como se ha dicho antes el consumo de tabaco y de alcohol son por lejos los factores de riesgo más importantes y su combinación tiene un efecto sinérgico sobre el riesgo, en particular en el SC (97) .…”
Section: Anfamed -Issn: 2301-1254unclassified
“…The main risk factors for OSCC are tobacco smoking (including swallowed toxins from cigarette smoke) and alcohol overconsumption, particularly when in combination. 12 Among dietary factors, fruit and vegetable intake is protective, 13 while intake of red meat 14 and very hot beverages are risk factors. 15 Genetic factors are also involved; a pooled analysis of three genome-wide association studies found new susceptibility loci for OSCC.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%